2015
DOI: 10.1177/1740774515609290
|View full text |Cite
|
Sign up to set email alerts
|

Should consent forms used in clinical trials be translated into the local dialects? A survey among past participants in rural Ghana

Abstract: The practice of translating informed consent forms into undeveloped local dialects and giving such copies to trial participants to send home needs to be re-evaluated. In populations where the written forms of local dialects are undeveloped and literacy is low, the use of local dialect versions of informed consent forms could ironically enhance the vulnerability of trial participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…In this study, Morrow and colleagues showed that most participants in South Africa perceive medical research to be similar to medical care, and may not understand the study purpose and therefore caregivers believed that their infants would be protected from HIV if they joined the research project. Similar findings were reported by Moodley et al [48]In Ghana, Baiden et al [49], Malawi, Bentley [59] South Africa, Ndebele et al [41], and Moodley et al [60] reported that most clinical trials with complex study procedures or consent forms tended to evaluate the understanding or recall of specific scientific and technical trial terms including randomisation, placebo. In Ghana, O [57] reported varied comprehension levels of disclosed information among participants and variability was also observed among younger and older participants.…”
Section: Ic Assessment Toolssupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, Morrow and colleagues showed that most participants in South Africa perceive medical research to be similar to medical care, and may not understand the study purpose and therefore caregivers believed that their infants would be protected from HIV if they joined the research project. Similar findings were reported by Moodley et al [48]In Ghana, Baiden et al [49], Malawi, Bentley [59] South Africa, Ndebele et al [41], and Moodley et al [60] reported that most clinical trials with complex study procedures or consent forms tended to evaluate the understanding or recall of specific scientific and technical trial terms including randomisation, placebo. In Ghana, O [57] reported varied comprehension levels of disclosed information among participants and variability was also observed among younger and older participants.…”
Section: Ic Assessment Toolssupporting
confidence: 80%
“…This led to two interrelated issues with the language in IC forms; the words or terms used by local communities and the translation of them into local languages to make them more accessible. The studies reviewed reported misunderstandings and miscommunication, especially when investigators and participants speak different languages, when IC documents have to be translated, or when scientific research and the notion of IC are unfamiliar to study participants [33,37,40,42,[49][50][51][52][53].…”
Section: The Language Used and The Translation Of Icmentioning
confidence: 99%
See 1 more Smart Citation
“…However, informed consent in the local language should be provided for a better understanding of the research and participation. [ 19 ] In that case, the consent form in the local language may be provided as an additional attachment with a clear description that the consent is available in the local language in the attached portable document format file. However, the major limitation of the informed consent process in an online survey is that the researchers do not have any idea how much the participant understands the consent form.…”
Section: Discussionmentioning
confidence: 99%